Growth curves for school children from Kuching, Sarawak: a methodological development - Mohamed, A.M.; Merican, Amir Feisal; Bonn Bong, Y.; Ahmad Shariff, A. (SAGE Publications, 2012)
In this article, the authors propose reference curves for height and weight for school children in the Kuching area, Sarawak. The school children were from primary to secondary schools (aged 6.5 to 17 years old) and comprised both genders. Anthropometric measurements and demographic information for 3081 school-aged children were collected (1440 boys and 1641 girls). Fitted line plots and percentiles for height and weight (3rd, 10th, 25th, 50th, 75th, 90th, and 97th percentiles) were obtained. The height of school boys and school girls were almost similar at the start of their school-going age. For school girls, height and weight values stabilized when they reached 16 or 17 years old but kept increasing for school boys. School boys were taller than school girls as they entered adolescence. Height differences between school boys and school girls became significantly wider as they grew older. Chinese school children were taller and heavier than those of other ethnic groups.